2012
DOI: 10.1158/1535-7163.mct-11-0529
|View full text |Cite
|
Sign up to set email alerts
|

MK1775, a Selective Wee1 Inhibitor, Shows Single-Agent Antitumor Activity against Sarcoma Cells

Abstract: Wee1 is a critical component of the G2/M cell cycle checkpoint control and mediates cell cycle arrest by regulating the phosphorylation of CDC2. Inhibition of Wee1 by a selective small molecule inhibitor MK1775 can abrogate G2/M checkpoint resulting in premature mitotic entry and cell death. MK1775 has recently been tested in preclinical and clinical studies of human carcinoma to enhance the cytotoxic effect of DNA damaging agents. However, its role in mesenchymal tumors, especially as a single agent has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
112
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 36 publications
19
112
1
Order By: Relevance
“…S1B). Also, Wee1 inhibition resulted in reduced levels of Cdk2 phosphorylation at Tyr-15, and elevated γ-H2AX levels as described (25). MK-1775-induced cell death was visible from 6 h of treatment onwards, as evidenced by PARP cleavage (Fig.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…S1B). Also, Wee1 inhibition resulted in reduced levels of Cdk2 phosphorylation at Tyr-15, and elevated γ-H2AX levels as described (25). MK-1775-induced cell death was visible from 6 h of treatment onwards, as evidenced by PARP cleavage (Fig.…”
Section: Resultssupporting
confidence: 54%
“…4). Multinucleation upon Wee1 inhibition was previously noted, although it was suggested that these effects might have resulted from S-phase defects (25,44). However, our data show that the aberrant mitotic exit was not caused indirectly by defective S-phase progression, because addition of Wee1 inhibitor during release from a nocodazole-induced mitotic arrest showed near-complete cytokinesis failure (Fig.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…MK-1775 monotherapy has been previously documented by Kreahling et al (30) where tumor explants treated with 500 nM MK-1775 for 24 hours demonstrated decreased CDK1 phosphorylation and features of cell death. Building on these results, here we have used multiple tumor derived cell lines and a flank PDX model to assess the effectiveness of monotherapy with MK-1775 in in vitro and in vivo models of GBM with a range of characteristics, Table 1.…”
Section: Discussionmentioning
confidence: 80%
“…At 1 µM MK-1775 treatment, the cell counts were 17.8% (p=1.3E-6) and 15.7% (p=3.6E-6) of the DMSO control treatment for MGPP6 and MGPP7, respectively. This dose was used throughout, similar to a study treating sarcoma cells with MK-1775 as a single agent at 500 nM (30). Treatment with MK-1775 effectively decreased levels of phosphorylation at CDK1 Y15, indicating on-target inhibition of Wee1, Figure 3D and Supplementary Figure S4B.…”
Section: Resultsmentioning
confidence: 99%